Identification of causal agent of tomato wilt and fruit rot (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2012)
Tomatoes are parasitized by a host of pathogens, including Fusarium oxysporum f. sp. lycopersici, the causal organism of fusarium wilt. Fresh vegetable fruits can be contaminated with various fungi which produce mycotoxins, important issue for human health. The objective of this paper was to isolate, determine, and identify the causal organisms of tomato wilt and fruit rot, based on the pathogen’s morphological and molecular characteristics. Samples of diseased plants showing the symptoms of tomato wilt were collected from different localities in the production region of Vojvodina. Fruits with symptoms of fusarium rot were collected from the storage and warehouses. The isolation and morphological determination of the fungus were performed on the PDA and Czapek' s nutrient media. Isolates from diseased plants growing in field, designated as TFW1-TFW12 and seven isolates from diseased tomato fruits (TFM1-TFM7) were chosen for further estimation. In determining the fungal isolates, the polymerase chain reaction (PCR) was also used. The EF1/EF2 primer pair was used for the molecular identification of F. oxysporum isolates. The nine analyzed samples were found to contain DNA fragments 700 bp in size, which are characteristic of the fungus Fusarium oxysporum.
Keywords: Wilts; Tomatoes; Nutrients; Isolation; Fusarium; Fruits